Avaliação do licenciamento ambiental de grandes projetos de saneamento básico na Região Metropolitana de Belém-PA - COSTA FILHO, Felipe Antonio Melo da (Universidade Federal do Pará, 2019)
The procedures of the environmental licensing process of four major basic sanitation projects carried out in the last 15 years and directly or indirectly affected or affected with a quality of life of over 100,000 inhabitants of the Belém Metropolitan Region were taxed. The methodology was divided into three stages, starting with a selection of basic sanitation ventures. In the second stage, the evaluation criteria were identified and systematized observing the current legislation and the technical-scientific literature. In the last stage, they were evaluated and classified as the effectiveness of the licensing processes in the competent environmental agency. The projects selected and analyzed were the projects of the Tucunduba Drainage Channel, Bologna Water Treatment Plant, Marituba Waste Processing and Processing Plant and UNA Sewage Treatment Plant. The environmental impact assessments applied in the four projects were consistent and adequate, regarding the effectiveness rating, the Bologna Water Treatment Plant process was rated as good, Marituba Waste Processing and Processing Plant and the Tucunduba Drainage Channel as regular and the UNA Sewage Treatment Plant had the worst result about the effectiveness of the environmental licensing process. In a survey, it was observed that compliance with legal standards occurs, despite the difficulties applied by the current project evaluation system, such as the lack of more technicians in the environmental agencies, lack of standardization of projects for small projects and small supervision. in the implementation and operation stages of the activities. There was also a long period of environmental analysis of the projects. Finally, it was selected that there is a need to improve or access the technical information and documents of the licensing processes of 4 projects, or that hinders the monitoring and participation of the directly affected population in the study area.